Massively parallelized molecular force manipulation with on-demand thermal and optical control - Su, H; Brockman, JM; Duan, Y; Sen, N; Chhabra, H; Bazrafshan, A; Blanchard, AT; Meyer, T; Andrews, B; Doye, JPK; Ke, Y; Dyer, RB; et al. (American Chemical Society, 2021)
In single-molecule force spectroscopy (SMFS), a tethered molecule is stretched using a specialized instrument to study how macromolecules extend under force. One problem in SMFS is the serial and slow nature of the measurements, performed one molecule at a time. To address this long-standing challenge, we report on the origami polymer force clamp (OPFC) which enables parallelized manipulation of the mechanical forces experienced by molecules without the need for dedicated SMFS instruments or surface tethering. The OPFC positions target molecules between a rigid nanoscale DNA origami beam and a responsive polymer particle that shrinks on demand. As a proof-of-concept, we record the steady state and time-resolved mechanical unfolding dynamics of DNA hairpins using the fluorescence signal from ensembles of molecules and confirm our conclusion using modeling.